The Effect of Effectiveness of Digital Campaign Budget, Selection of Digital Campaign Platform, and Increasing Brand Awareness on Purchase Intention of Optik Melawai Products - Muhammad Agung Hidayatullah; Lamhot Henry Pasaribu (Institute of Computer Science (IOCS), 2021)
This study aims to analyze 1) 1. Does the effectiveness of the budget campaign have a positive and significant impact on Optik Melawai's brand awareness?, 2. Does choosing the right digital campaign platform have a positive and significant impact on Optik Melawai's brand awareness? 3. Does brand awareness have a positive and significant impact on purchasing decisions for Optik Melawai products? In data search, questionnaires are used and distributed to people who are optical users and understand digital campaign budgets, digital campaign platforms, brand awareness and also purchase intention, where respondents are domiciled in Greater Jakarta in particular and several other big cities around the area. The sampling method in this study was purposive sampling, with a total sample of 153 people. In this study, the data analysis method used was PLS-SEM. This study shows that the digital campaign budget and the selection of the right digital campaign platform have a positive and significant effect on the purchase intention of optical customers in Indonesia. The results of this research can be a contribution for the Optik Melawai company to maximize the digital campaign budget and also the selection of the right digital campaign platform, to further increase brand awareness that will direct these customers to buy Optik Melawai products.